Crafting Turkish national identity, 1919-1927 - Morin, Aysel, author.
1 online resource.
Keywords: "Examining Mustafa Kemal Atatürk's Büyük Nutuk (The Great Public Address), this book identifies the five founding political myths of Turkey: the First Duty, the Internal Enemy, the Encirclement, the Ancestor, and Modernity. Offering a comprehensive rhetorical analysis of Nutuk in its entirety, the book reveals how Atatürk crafted these myths, traces their discursive roots back to the Orkhon Inscriptions, epic tales, and ancient stories of Turkish culture, and critiques their long-term effects on Turkish political culture. In so doing, it advances the argument that these myths have become permanent fixtures of Turkish political discourse since the establishment of Turkey and have been used by both supporters and detractors of Atatürk. Providing examples of how past and present leaders, including Recep Tayyip Erdoğan, a vocal critic of Atatürk, have deployed these myths in their discourses, the book offers an entirely new way to read and understand Turkish political culture and contributes to the heated debate on Kemalism by responding to the need to go back to the original sources - his own speeches and statements - to understand him. Contributing to emerging discourse-based approaches, this book is ideal for scholars and students of Turkish Studies, History, Nationalism Studies, Political Science, Rhetorical Studies, and International Studies"--